A Literature Review of Virtual Reality Exergames for Older Adults: Enhancing Physical, Cognitive, and Social Health - Xiacheng Song; Nazlena Mohamad Ali; Mohamad Hidir Mhd Salim; Muhammad Yudhi Rezaldi (Applied Sciences)
Virtual reality (VR) sports games are increasingly becoming important tools for enhancing cognitive and physical health among older adults. However, current research faces several challenges. Many experimental studies utilize existing games designed for general populations, lacking those specifically tailored for older adults; small sample sizes limit the generalizability of results; and issues such as cybersickness and technology adaptability remain challenges, although progress has been made. This literature review employs the PRISMA method to assess the latest research findings on the impact of VR sports games in improving cognitive and physical functions in older adults. We conducted a search in the Web of Science and SCOPUS databases, selecting literature related to VR interventions for balance, muscle strength, memory, and concentration enhancement. From an initial pool of 1705 articles, 12 studies met the inclusion criteria. Results indicate that VR sports games significantly enhance older adults’ exercise motivation through immersive experiences, while real-time feedback promotes the simultaneous improvement of cognitive and physical abilities. Furthermore, the social interaction elements within the VR environment effectively alleviate feelings of loneliness and enhance engagement longevity. Future research should focus on developing personalized and collaborative VR game designs and exploring their applications in home rehabilitation and community care to enhance accessibility and long-term effects. This review provides theoretical and practical support for the innovative application of VR technology in promoting healthy aging. It will benefit technology developers and researchers focused on the cognitive and physical health of older adults.